A multi-proxy analysis of the Holocene humid phase from the United Arab Emirates and its implications for southeast Arabia's Neolithic populations - Preston, GW; Thomas, DSG; Goudie, AS; Atkinson, OAC; Leng, MJ; Hodson, MJ; Walkington, H; Charpentier, V; Méry, S; Borgi, F; Parker, AG (Elsevier, 2015)
An early-to mid-Holocene humid phase has been identified in various Arabian geo-archives, although significant regional heterogeneity has been reported in the onset, duration and stability of this period. A multi-proxy lake and dune record from Wahalah in the United Arab Emirates (UAE) documents significant variations in hydrology, biological productivity and landscape stability during the first half of the Holocene. These data reveal that post-Last Glacial Maximum dune emplacement continued into the earliest part of the Holocene, with the onset of permanent lacustrine sedimentation at the site commencing ∼8.5 ka cal. BP. A long-term shift towards more arid conditions is inferred between ∼7.8 and 5.9 ka cal. BP, with intermittent flooding of the basin and distinct phases of instability throughout the catchment area. This transition is linked to the southwards migration of the Intertropical Convergence Zone (ITCZ) and associated weakening of monsoon rains. A peak in landscape instability is recorded between ∼5.9 and 5.3 ka cal. BP and is marked by a pronounced increase in regional dune emplacement. These variations are considered alongside the record of human settlement raising important questions about the interactions between population demographics, climate and environment in southeast Arabia during the Neolithic.